2021
DOI: 10.1186/s13195-020-00750-y
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10 plasma levels predict worsening in cognition of older adults: a 3-year follow-up study

Abstract: Background Blood-based biomarkers for Alzheimer’s disease (AD) are highly needed in clinic practice. So far, the gold standards for AD diagnosis are brain neuroimaging and beta-amyloid peptide, total tau, and phosphorylated tau in cerebrospinal fluid (CSF); however, they are not attractive for large-scale screening. Blood-based biomarkers allow an initial large-scale screening of patients under suspicion that could later be tested for the already established CSF biomarkers. To this regard, in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…We found significant single differences in some of the kits comparing AD and controls (toward higher levels in the AD group), with male patients exhibiting higher levels than females, or early-onset AD cases showing higher levels than late-onset patients. Increased CSF and plasma levels in mild AD cases has been reported by Pereira Vatanabe et al [ 19 ], and a prospective study suggests that higher baseline plasma levels are predictive of cognitive decline [ 33 ]. The higher ADAM10 levels found in men could be meaningful considering AD is more prevalent among women; this result could be interpreted as suggestive of a protective biochemical phenotype in males.…”
Section: Discussionmentioning
confidence: 96%
“…We found significant single differences in some of the kits comparing AD and controls (toward higher levels in the AD group), with male patients exhibiting higher levels than females, or early-onset AD cases showing higher levels than late-onset patients. Increased CSF and plasma levels in mild AD cases has been reported by Pereira Vatanabe et al [ 19 ], and a prospective study suggests that higher baseline plasma levels are predictive of cognitive decline [ 33 ]. The higher ADAM10 levels found in men could be meaningful considering AD is more prevalent among women; this result could be interpreted as suggestive of a protective biochemical phenotype in males.…”
Section: Discussionmentioning
confidence: 96%
“…This was found to be correlated with lower levels of APP processing in the non-amyloidogenic pathway as evidenced by reduced sAPPα (Agüero et al, 2020 ). In a longitudinal study of older adults, low levels of active ADAM10 correlated with a decline in cognitive abilities (Oliveira Monteiro et al, 2021 ). Moreover, ADAM10 is interrelated to the disease as levels of ADAM10 are reduced in AD patients (Colciaghi et al, 2002 , 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in plasma levels of ADAM10 have been shown to predict the deterioration of cognitive function in older adults. 26 Serum ADAM10 levels have also been evaluated as a biomarker for malignancy like colorectal cancer. 27 In diabetes, it has been suggested that urinary ADAM10 might be a biomarker of early diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%